Aortopulmonary fistula in a Warmblood mare associated with an aortic aneurysm and supravalvular aortic stenosis - Saey, Veronique (J Vet Intern Med, 2020)
This case report describes the clinical presentation, the necropsy findings, and genetic results of a 13‐year‐old Warmblood mare presented with colic and a bilaterally loud, holosystolic murmur. Echocardiographic examination revealed the presence of a thoracic aortic aneurysm, an aortic pseudoaneurysm, a periaortic hematoma (circumferential cuffing by perivascular hemorrhage), and aortopulmonary fistulation. A supravalvular aortic stenosis (SVAS) was visible during echocardiography. Necropsy confirmed that the thoracic aortic aneurysm had ruptured and connected to the pseudoaneurysm, which fistulated into the pulmonary artery. Histologically, the aneurysm wall revealed chronic lesions such as fibrosis, mucin depositions, mineralizations, and elastin fragmentation. The mid abdominal aorta showed lesions suggestive of a systemic elastin arteriopathy. Molecular analysis, however, could not attribute this disease to a variant in the elastin gene, the most common causative gene for SVAS. To the authors' knowledge, this case report describes a case of aortopulmonary fistulation in a Warmblood horse associated with the presence of SVAS and an aortic aneurysm.